A comparison of childbirth self-efficacy, fear of childbirth, and labor pain intensity between primiparas and multiparas during the latent phase of labor: a cross-sectional study - Yue Huang; Yuehua Zhong; Qiaozhu Chen; Jun Zhou; Bailing Fu; Yongfang Deng; Xianfang Tu; Yingfang Wu (BMC Pregnancy and Childbirth, 2024)
Abstract Background Childbirth is a long-lasting physiological stress. As one of the main stressors, labor pain exists throughout the whole process. Childbirth self-efficacy is the confidence, or belief that they can manage pain during childbirth. This sense of self-efficacy determines how pregnant women deal with labor pain and enables them to regulate their behavior and actively deal with childbirth. However, the difference in pain sensitivity between single births (primiparas) and multiple births (multiparas) has rarely been investigated. Objectives This study is aimed at investigating self-efficacy, fear of childbirth, labor pain of primiparas and multiparas and exploring factors related to the perceived labor pain intensity of pregnant women. Design Prospective cross-sectional study. Setting(s) Labour and delivery in a large academic specialized hospital in Guangzhou, China. Participants A total of 347 women, (182 primiparas and 165 multiparas) were enrolled in the data analysis. Pain was assessed before cervical dilatation (cervical dilatation ≤ 3 cm for the first delivery and ≤ 2 cm for the second delivery). Method The general information of participants was obtained by questionnaire and obstetrical records of the subjects were obtained from the electronic medical records extracted from the electronic medical record system (EMRS). Childbirth self-efficacy, fear of childbirth (FOC) and labor pain were compared between primiparas and multiparas. Paired t-test, chi-square test, Mann–Whitney test, univariate and multivariate regression analysis were used to analyze labor pain between the two groups and investigate factors related perceived labor pain intensity. Results The total scores related to fear of childbirth, fetal health, self-control, and labor pain injury of multiparas were notably reduced compared with primiparas (all P < 0.05). The perceived labor pain intensity and duration of the first stage of labor was reduced in the multipara group compared with the primipara group. The childbirth control sense of the multipara was better than that of the primipara. The perceived labor pain intensity was negatively correlated with advanced age (age ≥ 35 years), self-efficacy score, family support, and education (all P < 0.05). In contrast, the perceived labor pain intensity was positively correlated with tension, severe fear of childbirth, and anxiety (P < 0.05). Self-efficacy, gravidity, delivery cognition, and fear of childbirth were independent risk factors for the perceived labor pain intensity in the latent period (all P < 0.05). Conclusions Fear of childbirth is a predictor of perceived labor pain intensity. The extent of labor pain (minimum and maximum) can be predicted by the level of fear the expectant mother has. During the latent phase of labor, self-efficacy, fear of childbirth and labor pain are different between primiparas and multiparas.